INISIASI APOTEKER KELUARGA UNGGULAN DENGAN PENDEKATAN REAL TEACHING ACTION DI DESA SENDANG - Khoiry, Qisty Aulia; Ulfa, Fathya; Wulandari, Wening; Syafira, Muthia; Sasongko, Heru (Jurnal BALIRESO, 2019)
Rational drug use is a very warm discussion in the health care system in Indonesia. This is possiblebecause of reports of the occurrence of errors in the selection and use of drugs freely by thecommunity without based on adequate knowledge, causing undesirable side effects. Real TeachingAction (RTA) is an effort to improve people's knowledge through short learning activities aboutdrug information. The information conveyed among others is about the classification of drugs, thesteps to use the drug "DAGUSIBU" (Get, Use, Save and Dispose of), self-medication and route ofadministration of the drug. The measurement method used is a pretest and posttest design tomeasure the success rate of the program which is divided into 5 measurements. The location usedas an activity is in Sendang Village, Purwantoro Subdistrict, Wonogiri Regency, Central Java, withthe target of housewives who are then referred to as AKU (Superior Family Pharmacists) cadres.The results of the activity are known to have increased the knowledge of respondents throughpretest-posttest with a percentage value of 27.19% - 97%. So it can be concluded that the RTAapproach is able to provide a good understanding of AKU cadre training